2021
DOI: 10.1182/blood.2020009497
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of CD44 antibodies in murine immune thrombocytopenia is mediated by Fcγ receptor inhibition

Abstract: Monoclonal IgG antibodies to CD44 (anti-CD44) are anti-inflammatory in numerous murine autoimmune models but the mechanisms are poorly understood. Anti-CD44 anti-inflammatory activity shows complete therapeutic concordance with intravenous immunoglobulin (IVIg) in treating autoimmune disease models, making anti-CD44 a potential IVIg alternative. In murine immune thrombocytopenia (ITP), there is currently no mechanistic explanation for anti-CD44 activity although anti-CD44 ameliorates disease similarly to IVIg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Thus, these combined effects of heightened FcγR-mediated platelet destruction with increased inflammatory signaling in Adap −/− macrophages aggravate the development of thrombocytopenia. In supporting this notion, a recent study suggested that an anti-inflammatory antibody, anti-CD44, ameliorates ITP by inhibiting macrophage FcγR-mediated phagocytosis of platelets after its Fc fragment blocking FcγR IgG binding site (the Kurlander phenomenon) [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these combined effects of heightened FcγR-mediated platelet destruction with increased inflammatory signaling in Adap −/− macrophages aggravate the development of thrombocytopenia. In supporting this notion, a recent study suggested that an anti-inflammatory antibody, anti-CD44, ameliorates ITP by inhibiting macrophage FcγR-mediated phagocytosis of platelets after its Fc fragment blocking FcγR IgG binding site (the Kurlander phenomenon) [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to ENSEMBL, the lead SNP rs149514849 is located on the binding site of a transcription factor, and has been associated with variations of the expression of CD44 in macrophages. CD44, a pleiotropic glycoprotein involved in cell-cell interactions, cell adhesion and migration, has a role in the phagocytic process of macrophages [57, 58]. Additionally, the lead SNP rs76559378 at 13q13 is in strong LD ( r 2 = 0·897) with the exonic KL SNP rs201936594 (same GWAS, p = 9·74 x 10 -7 ) which displays a CADD score of 13·94, suggesting a likely deleterious effect.…”
Section: Resultsmentioning
confidence: 99%
“…Our lead SNP (rs149514849) may influence the expression of CD44, a pleiotropic glycoprotein involved in cell-cell interactions, cell adhesion and migration, and has a role in phagocytosis by macrophages. 82 , 83 Through our mapping strategy, we also identified CD59, whose expression is decreased on Plasmodium -infected erythrocytes, which may promote erythrophagocytosis. 84 LMO2 enhances erythropoiesis, 85 and IL1RAP upregulates the expression of the "don't eat me" signal CD47 to inhibit macrophage phagocytosis.…”
Section: Discussionmentioning
confidence: 99%